2018
DOI: 10.1055/s-0037-1610209
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Synthesis of Hetero- and Carbocyclic Compounds­ and Complexes Based on Acenaphthylene-1,2-dione

Abstract: Acenaphthylene-1,2-dione has been utilized in a wide range of reactions as a starting material for the synthesis of hetero- and carbocyclic compounds and complexes. This review provides a short summary of the recent advances in the application of acenaphthylene-1,2-dione in the synthesis of hetero- and carbocyclic systems and bioactive compounds. In addition, the applications of acenaphthylene-1,2-dione in the synthesis of spiro compounds, propellanes, and ligands in catalyst reactions, from 2002 to early 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Our interest in the application of acenaphthoquinone-derived azomethine ylides 16,17 and their reactions with -nitrostyrenes stemmed from extensive studies conducted on acenaphthoquinone. 18,19 This research ultimately resulted in the synthesis of derivatives of 4′-nitro-2H-spiro[acenaphthylene-1,2′-pyrrolidine]-2-ones.…”
Section: Paper Synthesismentioning
confidence: 99%
“…Our interest in the application of acenaphthoquinone-derived azomethine ylides 16,17 and their reactions with -nitrostyrenes stemmed from extensive studies conducted on acenaphthoquinone. 18,19 This research ultimately resulted in the synthesis of derivatives of 4′-nitro-2H-spiro[acenaphthylene-1,2′-pyrrolidine]-2-ones.…”
Section: Paper Synthesismentioning
confidence: 99%
“…Carbocyclic compounds are one of the primary class of organic chemistry. These are extremely widespread, and many of them are of great practical importance, carbocyclic compounds are also used in the preparation of synthetic resins and plastics as well.…”
Section: Carbocyclic Iodidesmentioning
confidence: 99%
“…Literature survey showed that acenaphthaquinone and its derivatives were widely used as starting and intermediate materials for the production of different compounds that have pharmaceutical importance [21,22], pesticides, dyes, drugs, and versatile fluorescent chemosensor [23][24][25][26]. However, a few reports on acenaphthaquinone thiosemicarbazone derivatives were observed.…”
Section: Introductionmentioning
confidence: 99%